Virtual Reality Media in IPAS: A Problem-Based Learning Development Study for Grade 5 Students’ Critical Thinking - Lailatuz Zahra; Desyandri; Ardipal; Yeni Erita (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop Virtual Reality (VR)-based learning media integrated with the Problem-Based Learning (PBL) model for fifth-grade IPAS learning. VR was used to present contextual problems at the problem orientation stage, allowing students to explore phenomena immersively before engaging in inquiry and problem-solving activities. This study employed a Research and Development (R&D) approach using the ADDIE model and involved 56 teachers and students from four elementary schools in Padang Ganting and Atar. Data were collected through expert validation, practicality questionnaires, and effectiveness tests. Validation by three experts resulted in an average score of 91%, consisting of content validity (85%), media validity (97%), and language validity (92%), all categorized as highly valid. Practicality tests yielded teacher scores of 93–94% and student scores of 97%, indicating a highly practical category. Furthermore, the effectiveness analysis produced an average N-Gain score of 0.8 (high category). These findings indicate that integrating immersive VR visualization with the PBL model provides meaningful learning experiences and supports the development of students’ critical thinking skills. Therefore, the developed media is feasible, practical, and effective for elementary IPAS learning.